PM.42 Hepatitis C Associated Thrombocytopenia in Pregnancy: Pregnancy Management and Morbidity. (26th April 2013) - Monteith, C; Cooley, S; Lambert, J; Kelleher, B; Ainle, F Ni; Eogan, M
Abstract : Hepatitis C virus (HCV) is associated with massive worldwide morbidity and mortality. Recent studies have implicated HCV in pathogenesis of immune thrombocytopenia. 1 2 However, the impact in pregnancy has not been explored in detail. We looked at the impact of HCV on maternal platelet count, bleeding and multidisciplinary management of labour and delivery in a retrospective series of HCV-infected pregnant women. Women with a detectable HCV viral load were identified between 2009 and 2011. Platelet count and HCV viral load were determined at booking, 32/40 and delivery in HCV-infected women and controls. Thrombocytopenia was identified in 10.3% of HCV-infected pregnant women in comparison to only 2.1% of age-matched controls (p < 0.01). Mean platelet count at delivery was significantly lower in HCV-infected women compared with controls (p = 0.01). There was no significant difference in estimated blood loss (EBL) at delivery. Regional anaesthesia was performed in 73% of thrombocytopenic HCV-infected women. In the first study to date to investigate the impact of thrombocytopenia upon pregnancy management in HCV-infected women. We demonstrated a significantly higher frequency of thrombocytopenia and a significantly lower platelet count in HCV-infected pregnant women compared with controls. We recorded no significant fetal bleeding complications. Footnotes : 1 Rajan, S.K., B.M. Espina, and H.A. Liebman, Hepatitis C virus-related thrombocytopenia: clinical and laboratory characteristics compared with chronic immune thrombocytopenic purpura. Br J Haematol, 2005. 129(6): p. 818–24. 2 Zhang, W., et al, Role of molecular mimicry of hepatitis C virus protein with platelet GPIIIa in hepatitis C-related immunologic thrombocytopenia. Blood, 2009. 113(17): p. 4086–93.